LMT USV Toolbox, a Novel Methodological Approach to Place Mouse Ultrasonic Vocalizations in Their Behavioral Contexts—A Study in Female and Male C57BL/6J Mice and in Shank3 Mutant Females - de Chaumont, Fabrice; Lemière, Nathalie; Coqueran, Sabrina; Bourgeron, Thomas; Ey, Elodie (Frontiers in Behavioral Neuroscience, 2021)
Ultrasonic vocalizations (USVs) are used as a phenotypic marker in mouse models of neuropsychiatric disorders. Nevertheless, current methodologies still require time-consuming manual input or sound recordings clean of any background noise. We developed a method to overcome these two restraints to boost knowledge on mouse ultrasonic vocalizations. The methods are freely available and the USV analysis runs online at https://usv.pasteur.cloud. As little is currently known about their usage and structure during social interactions over long term and in unconstrained context. Here, we investigated mouse spontaneous communication by coupling the analysis of USVs with automatic labelling of behaviors. We continuously recorded during three days undisturbed interactions of same-sex pairs of C57BL/6J sexually naive males and females at 5 weeks and 3 and 7 months of age. In same-sex interactions, we observed robust differences between males and females in the amount of USVs produced, in the acoustic structure and in the contexts of emission. The context-specific acoustic variations emerged with increasing age. The emission of USVs also reflected a high level of excitement during social interactions. We finally highlighted the importance of studying long-term spontaneous communication by investigating female mice lacking Shank3, a synaptic protein associated with autism. While previous short-time constrained investigations could not detect USV emission abnormalities, our analysis revealed robust differences in the usage and structure of the USVs emitted by mutant mice compared to wild-type female pairs.